Haemophagocytic lymphohistiocytosis secondary to invasive pseudomonas infection - A. Pakeerathan; G. Selvaratnam; T. Sooriyakumar (Asian Journal of Internal Medicine)
Haemophagocytic lymphohistiocytosis (HLH) is a rare, life-threatening genetic condition in children or a secondary disease in adults. The inherited form of HLH is caused by defects in lymphocytes, involving both autosomal recessive and X-linked patterns. In contrast, secondary or acquired HLH typically arises in response to infections, autoimmune diseases, or lymphoid cancers, possibly, in genetically susceptible individuals. The exact mechanisms of secondary HLH remain unclear, and the condition often goes unrecognized and untreated. Here we discuss a case of pyrexia of unknown origin in an elderly south-Asian woman, complicated with HLH triggered by invasive pseudomonas infection. This case highlights the challenges in diagnosis, treatment and identifying the aetiology of HLH.